2007
DOI: 10.1542/peds.2006-2116
|View full text |Cite
|
Sign up to set email alerts
|

Language Ability in Children With Permanent Hearing Impairment: The Influence of Early Management and Family Participation

Abstract: Early management of permanent childhood hearing impairment results in improved language. Family participation is also an important factor in cases that are confirmed late, especially for children with severe or profound permanent childhood hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
72
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 17 publications
0
72
2
2
Order By: Relevance
“…1,19,[24][25][26] In contrast to other studies, 20,27,28 we did not find any significant association between narrative performance and variables relating to the severity of hearing loss, such as age at diagnosis, 25,29 age at start of hearing aid use, 30 length of speech and language therapy, and children's schooling. On the other hand, some other studies did not find an association between language measurements and severity of hearing loss, 25 age at diagnosis and age at start of hearing aid use.…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…1,19,[24][25][26] In contrast to other studies, 20,27,28 we did not find any significant association between narrative performance and variables relating to the severity of hearing loss, such as age at diagnosis, 25,29 age at start of hearing aid use, 30 length of speech and language therapy, and children's schooling. On the other hand, some other studies did not find an association between language measurements and severity of hearing loss, 25 age at diagnosis and age at start of hearing aid use.…”
contrasting
confidence: 97%
“…Other authors have demonstrated lower use of cohesion elements in oral narratives among hearing-impaired individuals. 18 Studies on other populations 3,4,9,[22][23][24][25][26][27][28] have also indicated that there is lower use of cohesion elements among individuals with language disorders.…”
mentioning
confidence: 99%
“…Additional details of management after confirmation of PCHI have been reported elsewhere. 25 All 63 children with typically developed hearing in the comparison group achieved at least level 1 on both narrative structure and content scores, indicating use of some story-telling conventions (Table III). The average score in the typically developed hearing group was significantly better on all measures in children with normal hearing than in children with PCHI (p<0.05), except that the number of sentences used and the use of low-frequency morphological endings were similar (p=0.978 and 0.475 respectively; Table III).…”
mentioning
confidence: 99%
“…Early identification of a hearing loss is an essential requirement to ensure optimal development in children (Moeller, 2000;Watkin et al, 2007). Screening for hearing in school-aged children is important to negate the influence of an undetected hearing loss that may affect a child's academic performance and socio-emotional well-being (Arlinger, 2003;Fellinger et.…”
Section: Introductionmentioning
confidence: 99%